Low income and outcome in idiopathic pulmonary fibrosis: An association to uncover. (July 2021) - Sesé, Lucile; Caliez, Julien; Annesi-Maesano, Isabella; Cottin, Vincent; Pesce, Giancarlo; Didier, Morgane; Carton, Zohra; Israel-Biet, Dominique; Crestani, Bruno; Dudoret, Stéphanie Guillot; Cadranel, Jacques; Wallaert, Benoit; et al.
Abstract: Background: Low income, a known prognostic indicator of various chronic respiratory diseases, has not been properly studied in idiopathic pulmonary fibrosis (IPF). We hypothesize that a low income has an adverse prognostic impact on IPF. Methods: Patients were selected from the French national prospective cohort COFI. Patients' income was assessed through the median city-level income provided by the French National Institute of Statistics and Economic Studies according to their residential address. Patients were classified in two groups as "low income" vs. "higher income" depending on whether their annual income was estimated to be < or ≥18 170 €/year (the first quartile of the income distribution in the study population). The survival and progression-free survival (PFS) of the groups were compared by a log-rank test and a Cox model in multivariate analysis. Results: 200 patients were included. The average follow-up was 33.8 ± 22.7 months. Patients in the low income group were significantly more likely to be of non-European origin (p < 0.006), and to have at least one occupational exposure (p < 0.0001), and they tended to have a higher cumulative exposure to fine particles PM2.5 (p = 0.057). After adjusting for age, gender, forced vital capacity at inclusion, geographical origin, and occupational exposure having a low-income level was a factor associated with a worse PFS (HR: 1.81; CI95% : 1.24–2.62, p = 0.001) and overall survival (HR: 1.49; CI95% : 1.0006–2.23, p = 0.049). Conclusions: Low income appears to be a prognostic factor in IPF. IPF patients with low incomes may also be exposed more frequently to occupational exposures. Highlights: IPF patients from "Low income" group were more frequently exposed to aerocontaminants. Low income was associated with a worse progression free survival and overall survival in IPF patients. As for other respiratory diseases, the income appears to be a prognostic factor in IPF.